PERBANDINGAN PENGEMBANGAN APLIKASI E-SAMSAT JAWA TIMUR (JATIM) DENGAN APLIKASI E-DEMPO DALAM PENERAPAN E-GOVERNMENT - Muhammad Fathur Rahman; Novia Kencana; M.Qur’anul Kariem (Governance, 2024)
This study aims to determine the comparison of the e-Samsat application of East Java Province and South Sumatra, especially regarding tax payments towards egovernment by comparing the development of the East Java e-samsat application with the E-dempo application in the application of E-government. Other e-samsat users, in addition to less efficient procedures, website system connection problems can also affect people's desire to be reluctant to use the program.  Qualitative research methods are used by looking at phenomena more broadly and deeply in accordance with what happens and develops in social situations, starting from the data collection methods used, namely observation, interviews, and also documentation. The results show that the East Java e-Samsat application is more complex than e-dempo which is still in the transaction stage while the East Java e-Samsat is already in the transformation stage. The East Java e-Samsat application and also e-dempo are considered more efficient in the use of the application because applicants who want to pay taxes no longer need to come to the samsat office in Indonesia because they can verify anywhere because it can be done 24 hours without a time limit which allows users of the East Java e-Samsat application to no longer need to come to the samsat office, while the e-dempo application is Samasat can provide full 24-hour online services which should allow users to verify data at the Samsat office and this cannot be done online which makes the e-samsat application more effective and efficient, in the use of the application and also after electronic payment.